Growth, Induced Changes in Final Demand, Educational Requirements, and Wage Differentials - Hershkowitz, M.; Sussman, Zvi (The Review of Economics and Statistics, 1971)
More specifically, section I develops a model for the analysis of the effect of changes in consumer demand on average educational requirements under rather restrictive assumptions. Some quantitative conclusions, based on income elasticities, input-output coefficients and capital-output ratios in the Israeli economy, are presented. Section II deals with the effect of changes in the composition of consumption on the demand for different levels of education, and their effect, in turn, on wage differentials. The discussion is based on the analysis and calculations of section I.